More than Just a Meal: Breakfast Club Attendance and Children’s Social Relationships - Defeyter, Margaret Anne; Graham, Pamela Louise; Russo, Riccardo (Frontiers in Public Health, 2015)
The health benefits of school food have been widely promoted in recent years while the social opportunities that surround eating occasions at school have received little attention. Breakfast clubs (BCs), which take place at the start of the school day, offer a unique opportunity for children to consume a breakfast meal on their school premises in the company of their peers. Alternatively, after-school clubs (ASCs), which take place on school premises at the end of the school day, whilst also providing children with social opportunities tend to focus on sports engagement and skill development. The aim of the current paper is to investigate whether attendance at BCs and ASCs has an impact on children’s friendship quality and experiences of peer victimization. BC attendees, ASC attendees, and non-attendees completed the Friendship Qualities Scale and the Multidimensional Peer Victimization Scale (MPVS) at two time points. Time-1 data were collected 2 months after the introduction of school clubs. Time-2 data were then collected on the same measures again 6 months later. Results of the analyses of Time-1 data showed no significant differences between groups on any of the measures at Time-1. However, at Time-2, BC attendees showed improved levels of friendship quality compared to the other two groups. Moreover, analysis of the MPVS data at Time-2 showed that children who attended BC or ASC experienced a decline in victimization across time. The current findings suggest that BC attendance facilitates the quality of children’s relationships with their best friend over time. Additionally, attendance at a breakfast or ASC was associated with a reduction in victimization over time. The results have implications for utilization of breakfast and ASCs to aid children’s social relationships in school over time.